2001
DOI: 10.1890/1051-0761(2001)011[0060:fiapad]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Foraging in a Patchy and Dynamic Landscape: Human Land Use and the White Stork

Abstract: In the agricultural landscapes of Europe, the White Stork (Ciconia ciconia) prefers to forage on meadows with short vegetation. Thus, food supply for the nestlings and, consequently, breeding success of this central‐place forager depend on the temporal and spatial mowing activities of farmers around the nest to generate a patchy and dynamic food availability. Using a spatially explicit model, we study the impact of different land use patterns on food supply and breeding success of a central‐place forager. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…To assess the share of each habitat category in the total foraging area of each pair we used 1:50 000 topographic maps. We firstly mapped position of each nest and then measured the area of each habitat type within the radius of 4 km around the nest, a distance that is usually not exceeded during foraging trips of white storks (Alonso, Alonso & Carrascal, 1991;Struwe & Thomsen, 1991;Böhning-Gaese, 1992;Dziewiaty, 1992;Johst, Brandl & Pfeifer, 2001;Moritzi et al, 2001). Numerous behavioural observations confirmed validity of this assumption for the studied stork population.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the share of each habitat category in the total foraging area of each pair we used 1:50 000 topographic maps. We firstly mapped position of each nest and then measured the area of each habitat type within the radius of 4 km around the nest, a distance that is usually not exceeded during foraging trips of white storks (Alonso, Alonso & Carrascal, 1991;Struwe & Thomsen, 1991;Böhning-Gaese, 1992;Dziewiaty, 1992;Johst, Brandl & Pfeifer, 2001;Moritzi et al, 2001). Numerous behavioural observations confirmed validity of this assumption for the studied stork population.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the challenge in addressing those factors will come from (1) the fact that Tree Swallows, and most likely other bird species, respond to resource and habitat features at a range of spatial scales that varies during the course of breeding; and (2) that agricultural landscapes are highly dynamic as they vary within and among years in both composition and configuration. Spatiotemporal dynamics of agricultural landscapes should be of particular relevance to the measurement of life-history and fitness components strongly related to foraging success as it will affect the distribution of food resources, foraging strategies, and the level of parental investment (Brickle et al 2000, Johst et al 2001. Lacking to consider the influence of spatial scale or landscape dynamics may incidentally have caused the equivocal results obtained by previous studies quantifying the influence of agricultural practices on the breeding success of farmland birds.…”
Section: Breeding Successmentioning
confidence: 99%
“…Here we present data from a long-term study on age-and density-dependent breeding dispersal in the White Stork Ciconia ciconia. White Storks are distributed throughout Europe during the breeding season (Van den Bossche et al 2002) and a significant proportion of the total population breeds in Eastern Europe (Chernetsov et al 2006); a sharp population decline has been observed since the 1970s (Kanyamibwa et al 1990, 1993, Senra & Ales 1992, Johst et al 2001. In most parts of its range the White Stork is a farmland or wetland species (Van den Bossche et al 2002) and the population decline is primarily attributed to changes in land use, specifically the intensification of agricultural practices and the extension of human settlements (Schaub et al 2004, Massemin-Challet et al 2006.…”
mentioning
confidence: 99%